Self-Determination of Liz’s Character in Elizabeth Gilbert’s Eat, Pray, Love - Tarwia Ulfa; Trikaloka Handayani Putri (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2018)
Abstract This study focuses on depicting self-determination performed by main character’s act and how her self-determination gives the impact to her existence. The self determination is the way she takes decision in love life, beliefe, and social life that give impact in her existence. The first problem talks about how Elizabeth Gilbert or Liz determines herself from the conflict in her life. The second will continue the impact she get from her self-determination. This research applies literary criticism in order to describe Self-Determination of Liz’s Character for her existentialism in the phrase, quotation, and statement that related with self-determination in the novel. To answer the problems, this study uses the theory of existentialism by Jean Paul Satre,especially in his book entitled Existentialism is Humanism. The data divides into 2 part that explain about what are the decision Liz take in love life, beliefe, and social life then the impact of her self-determination. The result from the first statement is Liz’s decision as her actualization to determine her destiny in life. Then the impact as her choise she takes is the circumstances she responsible. Key words: Self-determination, existentialism, Jean Paul Sartre, Eat, Pray, Love novel. Abstrak Penelitian ini berfokus pada penggambaran penentuan nasib sendiri yang dilakukan oleh tindakan utama dan bagaimana penentuan nasib sendiri berdampak pada keberadaannya. Penentuan nasib sendiri dari cara dia mengambil keputusan dalam kehidupan cinta, kepercayaan, dan kehidupan sosial yang memberi dampak pada keberadaannya. Masalah pertama berbicara tentang bagaimana Elizabeth Gilbert atau Liz menentukan dirinya dari konflik dalam hidupnya. Yang kedua akan melanjutkan dampak yang didapat dari penentuan nasib sendiri. Penelitian ini menggunakan kritik sastra untuk menggambarkan penentuan nasib sendiri karakter Liz untuk eksistensialismenya dalam frasa, kutipan, dan pernyataan yang terkait dengan penentuan nasib sendiri dalam novel. Untuk menjawab masalah tersebut, penelitian ini menggunakan teori eksistensialisme oleh Jean Paul Satre, khususnya dalam bukunya yang berjudul Existentialism is Humanism. Data dibagi menjadi 2 bagian yang menjelaskan tentang keputusan yang diambil Liz dalam kehidupan cinta, kepercayaan, dan kehidupan sosial kemudian dampak dari penentuan nasib sendiri. Pernyataan pertama adalah keputusan Liz untuk mewujudkan takdirnya dalam kehidupan. Maka dampak dari pilihannya yang dia ambil adalah situasi dia bertanggung jawab. Kata kunci: Penentuan nasib sendiri, eksistensialisme, Jean Paul Sartre, Eat, Pray, Novel cinta.